The Brazilian Military Dictatorship Against the Sateré-Mawé People of the Amazon (Interdisciplinary Studies Journal, 2024)
The paper is  the  outcome  of  collaborative  research  involving  a Sateré-Mawé researcher, non-Indigenous  researchers,  and  ancients  of  the  Sateré-Mawé people. The paper aimed to investigate the impacts of the Brazilian military dictatorship on the Sateré-Mawé indigenous people, from the State of Amazonas, in Northern Brazil, in the Central Amazonbased, on three ancestral categories of treatment: rituals, prayers and hunting. The theoretical-methodological assumptions anchored to decoloniality (and its anti-decoloniality antithesis) guided our methodological analysis. The results suggest that the Large Investment Projects (GPIs, Brazilian acronym), which have a developmental content in themselves, were carried out under the military regime (1964-1985) and only contributed to generating controversial, if not negative, effects on the Amazonian ethnic group. highlighted. These GPIs were a universal geopolitical action, in the middle of the Cold War, then implemented by the USA and its allies, to different degrees across the planet. The imposition affected Brazil and more specifically the indigenous people of the lowlands of South America who densify the Brazilian Central Amazon.
Keywords: Sateré-Mawé People; Military Dictatorship; Amazon; Brazil